Analysis of the Imposition of VAT on Business Through E-Commerce at KPP Bekasi Utara in 2021 - Teguh Santoso; Riri Julia (Yayasan Ilomata, 2022)
The development of the internet has created a new business, namely electronic commerce which has turned conventional commerce into an electronic-based business. Electronic commerce has taken away the efficiency of the market so that a business with a new dimension is formed. Electronic commerce can provide additional state revenue so that the government issues regulations regarding the collection of VAT on trade transactions through the electronic system. Objective: To analyzing the implementation of VAT collection on trade through an electronic system in an effort to increase tax revenue at KPP Pratama Bekasi Utara based on an analysis of the implementation, the obstacles faced, and the efforts made to overcome these obstacles. Methods: This research was descriptive qualitative. The data collection methods were Observation, Documentation, and interviews. Result: the implementation of VAT on Trading Through Electronic Systems in an Effort to Increase Tax Revenue at KPP Pratama Bekasi Utara has not been implemented optimally, because not all PMSE business actors know and apply regulations regarding VAT collection on PMSE transactions.